Popular Genres and Their Uses in Fiction - Wegrodzka, Jadwiga (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
The book focuses on popular genres of romance, fantasy, science fiction, dystopia, thriller, and What-if historical fiction in popular books, in artistic literature and on the borderline between the two. The author analyses the work of writers such as Jennifer Greene, Barbara Delinsky, and Lilian Darcy, Jennifer Lee Carrel, Michael Crichton, Ursula Le Guin, C. S. Lewis, Michel Faber and William Golding. She applies an analytical approach based on semiotics, structuralism and narratology and discusses genre mixture, adaptation and intertextuality, as well as world modelling.
Keywords: literární žánry; fikce; literary forms; fiction; elektronické knihy; electronic books